Implementing Clinical Guidelines for the Treatment of Psychosis: The Frontline Leaders’ Point of View. A Qualitative Study - Nordin HMA; Mathisen GE; Rørtveit K; Joa I; Johannessen JO; Ruud T; Hartveit M (Dove Medical Press, 2024)
Håkan MA Nordin,1,2 Gro Ellen Mathisen,3 Kristine Rørtveit,1,2 Inge Joa,1,4 Jan O Johannessen,1,4 Torleif Ruud,5,6 Miriam Hartveit7,8 1Department of Psychiatry, Stavanger University Hospital, Stavanger, Norway; 2Department of Caring and Ethics, University of Stavanger, Stavanger, Norway; 3Norwegian School of Hotel Management, University of Stavanger, Stavanger, Norway; 4Department of Public Health, University of Stavanger, Stavanger, Norway; 5Division of Mental Health Services, Akershus University Hospital, Lørenskog, Norway; 6Institute of Clinical Medicine, University of Oslo, Oslo, Norway; 7Department for Research and Innovation, Helse Fonna Health Trust, Valen, Norway; 8Department of Global Public Health and Primary Care, University of Bergen, Bergen, NorwayCorrespondence: Kristine RørtveitUniversity of Stavanger, Faculty of Health Sciences, Postbox 8600, Stavanger, 4036, Norway, Tel +4790521114, Email kristine.rortveit@uis.no; kristine.rortveit@sus.noBackground: Despite the large amount of leadership and implementation theories and recommendations, healthcare services continue to struggle with efficiently incorporating new knowledge. The questioning of conventional leadership approaches in healthcare organizations prompted us to investigate how frontline leaders comprehend their own implementation intentions and actions, and how these intentions and actions may impact the implementation of clinical guidelines in mental healthcare in Norway.Methods: Employing a theory-driven qualitative design, we conducted nine semi-structured interviews with frontline leaders who had recently led implementation of clinical guidelines for the treatment of psychosis in mental health. We employed Systematic Text Condensation, informed by Normalization Process Theory, to structure and analyze the data and used fidelity scales to measure the degree of implementation and distinguish between leaders' levels of success in implementation.Results: Frontline leaders in units that achieved high success in implementation described their intentions and actions differently, from those with less success. The former group's actions aligned more closely with the constructs of the Normalization Process Theory compared to the latter group when describing their actions. Frontline leaders leading units with a high degree of implementation success describe relation-orientation, trust, and providing adaptive space for staff members to take initiative. In contrast, those leading units with less implementation success describe more control and guidance of co-operators and place more emphasize on information and knowledge.Conclusion: Differences in how frontline leaders describe their actions and intentions to achieve clinical guideline implementation suggest that the leadership approach of these frontline leaders is an important factor to consider when planning and conducting implementation. To better understand the implementation process, it is important to pay attention to how frontline leaders customize their leadership approaches to the dynamics of complex organizations, and how they interact with their team and superiors.Plain Language Summary: Despite the large amount of available implementation theories and recommendations, healthcare services continue to struggle with efficiently incorporating new and better practice. The clinicians' closest leader, the Frontline leader, is considered to be in a unique position to manage and enable implementation in the complex healthcare system. The current study's aim was to improve our understanding of what these leaders do, and how they operate, to enable the implementation of clinical guidelines. We interviewed nine mental health service leaders in Norway with experience of leading implementation of clinical guideline during the last 3 years. We found a variety of leaders' intentions and actions regarding their involvement in the process and how they relate to their staff and superiors. Frontline leaders that lead units with high degree of implementation success described actions according to all four constructs of the Normalization Process Theory (Coherence, Cognitive participation, Collective action and Reflexive monitoring), while frontline leaders with less implementation success had more fragmented descriptions. Successful leaders appear to be more relation-oriented compared to those in less successful units. This suggests that leaders should focus on inter-personal dynamics, in addition to more concrete implementation interventions, to succeed.We recommend to take the leadership actions and intentions identified in this study into consideration when planning and evaluating implementation projects and leadership programs, as well as when recruiting frontline leaders.Keywords: complexity leadership theory, frontline leaders' implementation of clinical guidelines, normalization process theory, implementation fidelity